TRANSFORMASI “ALFU LAILAH WA LAILAH” - Eva Farhah (CMES (Center of Middle Eastern Studies), 2019)
This research tries to discover and reveal the transformation works from “Alfu Lailah wa Lailah”. The purpose of the discovery and disclosure of the works of transformation is to know the reader's attitude to the work "Alfu Lailah wa Lailah". The theory used in this research is intertextual theory with descriptive qualitative research method. The results show that the work "Alfu Lailah wa Lailah" has inspired writers, musicians, and choreographers, and literary enthusiasts to give birth to other similar works. The work of transformation in the form of prose found a number of 12 manuscripts, in the form of music of a number of 2 works, in the form of choreography of ballet 1, and in the form of film and animated film totaling 3 film.